The Dynamics of Public and Private Debt in Ghana - Aimola, Akingbade Urungbodi; Odhiambo, Nicholas M. (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2018)
This paper explores the dynamics of public and private debt in Ghana for the past 32 years. Ghana’s total public debt stock to Gross Domestic Product (GDP) ratio has remained above the 60.0% sustainability threshold recommended by the West Africa Monetary Zone (WAMZ) since 2013. Implemented bank reforms in the country show an upward trend for domestic credit to private sector by banks as a percentage of GDP. Using exploratory review approach, the paper identified fiscal dominance, cost of borrowing, deterioration in export earnings, ineffective fiscal, monetary and debt management policies coordination as factors responsible for changes in total public debt stock. On the other hand, increased domestic borrowings by government from the banks, and Deposit Money Banks’ (DMBs)’ adverse selection in private sector credit allocation affect changes in domestic credit to the private sector by banks. Of these causes, fiscal dominance is the major determinant of public and private debt in Ghana. The study, therefore, recommends that government should pursue fiscal operations that are necessary to put public debt on a declining path. In addition, effective coordination of fiscal, monetary and debt management policies need to be strengthened together with the autonomy of the Bank of Ghana in the use of its monetary policy instruments.